Prescribing habits in the pharmacotherapy of schizophrenia - King, Russell Wayne (My University, 2011)
Background: Many factors affect the prescribing of medication to patients with schizophrenia including variables that relate to physicians and may result in marked variance in the choice of drugs, dosages, drug combinations, route of administration and the use of antipsychotic, anticholinergic, sedative and other adjuvant drugs. Clinical practice guidelines were developed to address this variance and for other reasons, including the management of side-effects, drug innovation, rising costs, information overload, changes in treatment goals and the management of medication non-adherence. There are advantages and disadvantages to using clinical practice guidelines including those pertaining to context and cultural norms, but they remain the best method of assessing prescribing quality. Many guidelines are based on the results of randomised clinical trials (with a single drug) or are the consensus of experts in the field. Despite the development and publication of these guidelines over the past two decades, they are frequently not adhered to resulting in much variance in treatment. Aims and objectives: The aim of the study was to determine to what extent the prescribing of psychotropic drugs in the treatment of schizophrenia was consistent with the most recent version of each of five guidelines that originate outside South Africa (two from the United States and one each from Canada, the United Kingdom, and Australia and New Zealand); and one that was developed locally. Methodology: A retrospective, cross-sectional prescription chart review with data sampling at three time points (on hospital admission, at fourteen days thereafter and on hospital discharge) was undertaken. A sample population was drawn over a three year period during which the patients’ physician had access to the same drug formulary. Seventy patients met the study selection criteria in terms of age, diagnosis and receipt of antipsychotic medication during hospital stay and on discharge. Seventy patients met the study selection criteria, and their prescriptions for psychotropic medication (exclusively) were examined for a number of parameters including: drug class, drug name, dose, route of administration and whether the medication was to be administered routinely or ‘as needed’. Findings and discussion: As compared with the recommendations made in some or all of the guidelines, first generation antipsychotic agents were over-prescribed especially early on in the patients’ hospital stay, whereas second generation antipsychotics were under-prescribed. The profile changed after fourteen days and on discharge there were more patients on second generation drugs than on the older drugs. More patients were discharged on depot antipsychotic treatment than were admitted which is considered a favourable finding, however, many patients receiving the depot form continued to be prescribed the oral drug on a routine basis and for an indefinite period, resulting in antipsychotic polypharmacy. Anticholinergic drugs were prescribed as prophylaxis for the extra-pyramidal side-effects of the first generation antipsychotic drugs and more than a quarter of the sample received these drugs on discharge, after which they were to be taken routinely and indefinitely. A similar finding was made with the use of benzodiazepine sedatives, where nearly a quarter of patients received these drugs on discharge - again to be taken routinely and for an unspecified period. Sodium valproate was given increasingly to many patients in the sample and was prescribed to over a quarter of those upon discharge, without an indication of duration. Limitations: The study was retrospective in design, without the benefit of the patients’ clinical histories and treatment progress, and the findings were compared with guidelines whose age spanned more than a decade and some of which had become redundant. Conclusions: The study demonstrated some prescribing habits that were not in accord with the guidelines used for comparison in the study. The extent of the disagreement reveals the need for a prospective pilot study that will include the patients’ clinical progress in the study design which will provide greater insight into why specific medication parameters were chosen by the physician for the individual patient. If the findings justify it, then a programme promoting better adherence to the most current guidelines should be commenced.
M.Sc. (Med), Faculty of Health Sciences,University of the Witwatersrand, 2011
Keywords: schizophrenia; pharmacotherapy; prescribing habits